2019
DOI: 10.1038/s41419-019-1654-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the transcription factor receptor LXR to treat clear cell renal cell carcinoma: agonist or inverse agonist?

Abstract: Growing evidence indicates that clear cell renal cell carcinoma (ccRCC) is a metabolism-related disease. Changes in fatty acid (FA) and cholesterol metabolism play important roles in ccRCC development. As a nuclear transcription factor receptor, Liver X receptor (LXR) regulates a variety of key molecules associated with FA synthesis and cholesterol transport. Therefore, targeting LXR may provide new therapeutic targets for ccRCC. However, the potential regulatory effect and molecular mechanisms of LXR in ccRCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 64 publications
2
59
0
Order By: Relevance
“…In this context, LXR inhibition effectively impairs tumour growth by suppressing lipogenesis and glycolysis. Furthermore, the effects of both the LXR agonist LXR623 and the inverse agonist SR9243 on clear cell renal cell carcinoma have been examined 121 . Both drugs effectively decrease cancer cell proliferation and induce apoptosis.…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…In this context, LXR inhibition effectively impairs tumour growth by suppressing lipogenesis and glycolysis. Furthermore, the effects of both the LXR agonist LXR623 and the inverse agonist SR9243 on clear cell renal cell carcinoma have been examined 121 . Both drugs effectively decrease cancer cell proliferation and induce apoptosis.…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…The presence of apparent abnormalities in fatty acid metabolism in kidney cancer is recognized. In our previous studies, it was found that breaking the lipid homeostasis in this type of kidney cancer could significantly limit tumor progression [ 30 ]. Of course, many molecules clearly express correlations, and because of the limited space, they are not listed here.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we found that most of these genes have statistical significance in the prognosis of patients with KIRC. Due to our previous research involving KIRC 17 , we focused on the potential role of these genes, particularly their mRNA expression, in KIRC and displayed this information in the form of heat maps and violin diagrams. We used the online tool of the GSCALite website to map the TRIM family genes and cancer pathway regulatory network.…”
Section: Introductionmentioning
confidence: 99%